Space Maintainers Redefined: Contemporary Modifications and Trend - Neetika Singh; Enna Singla; Sanchit Kumar; Kamaljit Kaur; Salman Saleem; Reva Sharma (Dental Journal of Advance Studies)
The primary dentition plays a vital role in a child's overall growth and development by aiding in chewing, speech, esthetics, and acting as a natural space maintainer for the proper eruption of permanent teeth. However, conditions such as dental caries, trauma, resorption, or systemic diseases can lead to the early loss of primary teeth, potentially causing space reduction and malocclusion. Space maintainers (SM) help preserve arch length and width by preventing unwanted tooth movement. The concept of space maintenance was first introduced by JC Brauer in 1941. The choice of a space maintainer depends on factors such as dental spacing, the eruption timeline of the succeeding tooth, and orthodontic considerations. This article explores space maintainers, their classifications, and their clinical indications and contraindications.